Control of ideally expanded and under expanded nozzle flows with micro jets - G M, Fharukh Ahmed; Baig, Maugal Ahmed Ali; Bashir, Musavir; Khan, Sher Afghan (International Organization of Scientific Research ( IOSR ), 2016)
This paper presents an experimental investigation of an airflow from convergent-divergent axisymmetric nozzles expanded suddenly into circular duct of larger cross-sectional area than that of nozzle exit area, focusing attention on the base pressure and the flow development in the duct. To investigate the influence of active control on wall pressure as well as on the flow field developed in the duct, the micro jets of 1 mm orifice diameter located at 900 interval along a pitch circle diameter 1.3 times the nozzle exit diameter were employed as the controller of the base pressure. The Mach number investigated in the present study was 1.30. The area ratio of the present study was 2.56. The nozzle pressure ratio (NPR) used were from 2.77 and 4.16 respectively which corresponds to correct and under expanded conditions. The length-to-diameter ratio of the enlarged duct was varied from 10 to 1.The level of expansion at the nozzle exit (i.e. before sudden expansion) influences the wall pressure very strongly. When the micro jets were activated they found to influence the flow in the enlarged duct. Wall pressure results for correctly expanded and under expended jets indicate that the flow in the enlarged duct remains attached for L/Ds including at L/D =1. Also, it is found that the wall pressure flow field in the duct for with and without control are identical and the control in the form of the micro jets does disturb the flow field. Results for L/D = 8 and 10 for correctly expanded jets indicate peculiar phenomenon and are totally different from all the results for lower L/Ds. Wall pressure results for under expanded jets indicate that control results in marginal decrease in the wall pressure otherwise the wall pressure flow field with and without control remains same.